Signet ring carcinoma of ampulla of vater - Ardeshir Talebi (Advanced Biomedical Research, 2014)
Signet ring carcinoma is a common type of adenocarcinoma of stomach but its occurrence in ampulla of Vater is extremely rare. There are only a few previous reported cases of signet ring carcinoma of ampulla of Vater. Here we reported a 61-year-old woman with obstructive jaundice. Ultrasonography and computed tomography (CT scan) examination showed intra- and extrahepatic bile duct dilatation. Endoscopic examination with biopsies revealed a small-size mass in ampulla of Vater with diagnosis of signet ring carcinoma. On consequent pancreatoduodenectomy the tumor was diagnosed as T2N0M0, stage IB. Because of the specific site of signet ring carcinoma of ampulla of Vater, the tumor seems to present itself at an early stage of disease. We review in the literature to suggest our idea.